Melatonin Enhances the Postharvest Disease Resistance of Blueberries Fruit by Modulating the Jasmonic Acid Signaling Pathway and Phenylpropanoid Metabolites - Qu, Guangfan; Wu, Wenneng; Ba, Liangjie; Ma, Chao; Ji, Ning; Cao, Sen (Frontiers in Chemistry, 2022)
In this study, to investigated the physiological and molecular mechanisms of melatonin inhibiting postharvest rot of blueberries fruit. Blueberry fruits were dipped in 0.3 mmol L-1 melatonin solution for 3 min and stored at 0 °C for 80 days. The results indicated that melatonin did not significantly (P > 0.05) inhibit the mycelial growth or spore germination of Alternaria alternata, Botrytis cinerea, and Colletotrichum gloeosporioides. In addition, an in vivo study revealed that the melatonin treatment increased the enzymatic activities of phenylalanine ammonia lyase (PAL), cinnamate 4-hydroxylase (C4H), 4-coumarate-CoA ligase (4CL), cinnamyl alcohol dehydrogenase (CAD), polyphenol oxidase (PPO), and peroxidase (POD) in fruits. Further, genes related to jasmonic acid synthesis were upregulated (VaLOX, VaAOS, and VaAOC), as were those related to pathogenesis-related proteins (VaGLU and VaCHT) and phenypropane metabolism (VaPAL, VaC4H, Va4CL, VaCAD, VaPPO, and VaPOD), which promoted the accumulation of total phenols, flavonoids, anthocyanins, and lignin in the fruits. These results suggest that melatonin enhances the postharvest disease resistance of blueberry fruit by mediating the jasmonic acid signaling pathway and the phenylpropane pathway.